Conformational and electronic (AIM/NBO) study of unsubstituted A-type dimeric proanthocyanidin - Lobayan, Rosana M. (2008)
The conformational space of the unsubstituted A-type dimeric proanthocyanidin was scanned using molecular dynamics at a semiempirical level, and complemented with functional density calculations. The lowest energy conformers were obtained. Electronic distributions were analysed at a higher calculation level, thus improving the basis set. A topological study based on Bader’s theory (AIM: atoms in molecules) and natural bond orbital (NBO) framework was performed. Furthermore, molecular electrostatic potential maps (MEPs) were obtained and analysed. NMR chemical shifts were calculated at ab initio level and further compared with previous experimental values; coupling constants were also calculated. The stereochemistry of the molecule is thoroughly discussed, revealing the key role that hyperconjugative interactions play in defining experimental trends. These results show the versatility of geminal spin–spin coupling 2J(C-1′,O) as a probe for stereochemical studies of proanthocyanidins.